RESISTENSI DAN ADAPTASI MASYARAKAT ACEH DALAM MENJAGA IDENTITAS DARI HEGEMONI BARAT DI ERA GLOBALISASI - Muhammad Hilman Hirzi,; Muhammad Fajar Iskandar,; Machrus Hakim Nugroho , (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
Aceh has a long history of maintaining its Islamic identity since the era of the Samudera Pasai Sultanate. In the era of globalization, Acehnese society faces challenges from Western hegemony, which brings secular values ​​and modernization that have the potential to change local social and cultural structures. This study analyzes the response of Acehnese society to this phenomenon through two main mechanisms: resistance and adaptation. Resistance is reflected in the implementation of Islamic law, Islamic-based regulations such as the Aceh Qanun, and criticism of Western culture that is considered contrary to Islamic values. Meanwhile, adaptation is carried out by adopting global technology for the benefit of Islamic preaching, developing a sharia-based economy, and integrating a modern education system with Islamic values. By using a qualitative approach based on literature studies and the theoretical framework of Antonio Gramsci's hegemony, Henri Tajfel's social identity theory, and Syed Muhammad Naquib al-Attas' Islamization theory, this study finds that resistance and adaptation are not two conflicting concepts, but rather complementary strategies in shaping Aceh's Islamic identity amidst global dynamics. Islamization is the primary mechanism for integrating aspects of modernity with Islamic values, enabling Aceh to remain relevant while preserving the essence of its cultural identity.